Krytyka metodologiczna w ocenie dorobku habilitacyjnego - Hejnicka-Bezwińska, Teresa (Krytyka metodologiczna w praktyce tworzenia wiedzy, 2019)
“Methodological critique” is a form of scientific critique along with philosophical, empirical, theoretical or logical critique. It does not require any special justification to recognize this form of critique as the most important, the most meaningful and most decisive in assessing the postdoctoral achievements. In the summary, I refer only to one legal argument that obtaining a postdoctoral degree is a kind of “pass”, entitling one to adjudicate on the scientific achievements of others and to appear in various roles related to awarding (or refusing to award) the academic degree of a particular person. In the chapter, I present some of the most important questions to which I was seeking answers, assessing the work indicated as the main scientific achievement. This unitary example seems to be a good illustration of the problems, controversies and dilemmas appearing when one is preparing an opinion for a meeting of the Postdoctoral Degree Awarding Committee. Uncovering your own reflection on a specific work can be a contribution to the discussion of the reviewer’s role in the postdoctoral degree procedure and the place and role of methodological critique in this procedure, especially when the author of the indicated achievement has not shown due diligence to reliably present and authenticate his/her research concept.